A severe clinical case of theileriosis with terminal wasting in adult cattle: a veterinary clinical and pathology case report - Abdullah Jesse, Faez Firdaus; Yan, Chee Hor; Izzati, Uda Zahli; Paul, Bura Thlama; Mohd Lila, Mohd Azmi; Chung, Eric Lim Teik; Wan Ishak, Wan Mohd Sukri; Kanini, Md Nazim Razili; Jimale, Yonis Ahmed; Norsidin, Mohd Jefri (Malaysian Society of Applied Biology, 2024)
This veterinary clinical and pathology case report describes a severe clinical case of theileriosis in adult cattle with prolonged recumbency and terminal wasting because of complications due to chronic theileriosis in two adult (2-year-old) Jersey-Friesian Cross. The case was referred to the large animal clinic of the University Veterinary Hospital (UVH), Faculty of Veterinary Medicine, Universiti Putra Malaysia (UPM). The animals were presented as recumbent, dull, depressed, hypothermic, dehydrated, and cachexic. There were poor responses of the patients to fluid therapy and non-steroidal anti-inflammatory treatments, and they both died within 24 hrs of clinical presentation. Haematology (complete blood count and serum biochemistry) results revealed haemoconcentration and faecal examinations were negative for liver fluke infestation and blood smear examination was positive for intraerythrocytic piroplasms of Theileria (0.01% parasitaemia). Post-mortem examination further revealed advanced cachexia, generalised serous atrophy of fat, hepatomegaly, hepatic congestion, pulmonary congestion, and pulmonary oedema. Histological findings revealed atrophy of the hepatic cord, hepatic congestion, splenic hemosiderosis, pulmonary oedema and congestion. The clinicopathological findings supported an aetiological diagnosis of a severe clinical case of Theileriosis with terminal wasting because of complications due to chronic Theileriosis infection.